Gender-Responsive Policy in Water Management: An Outlook in ‘Citarum Harum’s Program - Sari, Suwarti; Oktaviani, Jusmalia; Aprillia, Bunga (Jurnal Ilmiah Hubungan Internasional, 2024)
In Indonesia, rivers, crucial for clean water, currently face alarming pollution. Unfortunately, women, key in ensuring water quality, lack opportunities. This study aims to depict the state of the Citarum River, women's involvement, and propose ways for women to optimize their role in managing domestic waste for river restoration. Using qualitative methods, the research identifies a connection between environmental issues and patriarchal challenges, emphasizing the need for comprehensive, gender-friendly policies. Recommendations from UN Water policies can be adapted for effective implementation in Indonesia. According to the research, the issue of the environment or water is a component of the traditional patriarchy problem, requiring gender-friendly strategies at all tiers. Even with initiatives to include women in areas such as water empowerment, women continue to be excluded from decision-making processes. Based on the research, it is recommended that women be made aware of their significance in gender-friendly policies and that their opinions should be considered during the decision-making process. Keywords: rivers, water quality, women's empowerment